Draft genome sequence of Diaporthe sp. strain HANT25, an endophytic fungus producing Mycoepoxydiene - Kan Tulsook (2020)
© 2020 Tulsook et al. Diaporthe sp. strain HANT25 is an endophytic fungus that produces mycoepoxydiene, a rare bioactive natural compound. Here, we report the genome sequence of Diaporthe sp. HANT25, comprising 55.3 Mb in 80 scaffolds. The genome sequence should enhance understanding of the biology and bioactive compound production potential of the genus Diaporthe.